Perancangan & Pengembangan Sistem Manajemen Akuntansi Berbasis Web pada UMKM Chibi Chef Batam - Diny Agustini Adnas; Charlie Aprilianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
The aim of this community services is to overcome the problem of accounting reports at Chibi Chef Batam. The problem of accounting reports occurs because Chibi Chef Batam do not have any accounting management system, usually Chibi Chef do manual recording so that make the problem arise such as not accurate report and takes a lot of time. The community services were started from November 1, 2020, to January 31, 2021, using interview, observation, and literature study as data collection techniques and using waterfall as software development method. This community services create a web-based accounting management system that can help the Chibi Chef Batam for records every transaction that occur and print accounting reports into soft copy as a format. After the system implementation at Chibi Chef Batam, Chibi Chef can print reports more efficient and accurately. The accounting management system for community services activities in the future are recommended to add archive or attachment for every transaction that recorded in the system as evidence that can help Chibi Chef Batam to validate transaction that occur